1987
DOI: 10.1039/an9871201007
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometric determination of germanium and phosphorus in siliceous materials after hydrofluoric acid distillation

Abstract: Hydrofluoric acid distillation has been applied to the determination of phosphorus and germanium in siliceous materials based on the formation of their heteropolymolybdates. Silicon and arsenic are separated by distillation from phosphorus, germanium and the remainder of the sample. The formation of colourless P2M050236-is employed to avoid the interference of phosphorus in germanium determination. Germanium is determined spectrophotometrically as its heteropolymolybdate and phosphorus gravimetrically by diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The methods used for the determination of trace amounts of germanium included spectrophotometry (Hernandis et al. 1987; Shen et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The methods used for the determination of trace amounts of germanium included spectrophotometry (Hernandis et al. 1987; Shen et al.…”
Section: Introductionmentioning
confidence: 99%
“…Later analyses, using more sophisticated technology, revealed that merely trace amounts of germanium in plants are used for Chinese medicine (Mino et al 1980). The methods used for the determination of trace amounts of germanium included spectrophotometry (Hernandis et al 1987;Shen et al 1987;Nukatsuka et al 1989) and atomic spectrometry (Fazakas 1984;Nakata et al 1988;. Atomic fluorescence spectrometry (AFS) is an emission technique, which relies upon radiation rather than thermal excitation of atomic vapor for its function.…”
Section: Introductionmentioning
confidence: 99%
“…A number of papers have dealt with determination of trace amounts of germanium, mainly by spectrometry. [2][3][4] Germanium has many oxygenated species in aqueous solution and is not well characterized polarographically. Previously we have reported some sensitive and/ or selective electroanalytical methods based on the utilization of polarographic maximum waves or catalytic maximum waves of analyte.s_8 In the case of molybdenum,9 for example, the detection limit reaches down to 10-10 mol dm-3.…”
mentioning
confidence: 99%